The Brady Plan and adjustment incentives - Helmut Reisen (Intereconomics, 1991)
The Brady Initiative has led to the conclusion of several debt-relief agreements. Opinion on the effects of these agreements on the debtor countries involved vary widely. The following article aims at clarifying the debate.
Keywords: 330; Indebtedness